Nutrition-sensitive value chains: A guide for project design - International Fund for Agricultural Development (International Fund for Agricultural Development, 2019)
A first-of-its-kind, this new Guide from IFAD presents practical, step-by-step guidance for shaping value chain projects to improve nutrition. The Guide highlights challenges and opportunities in establishing nutrition-sensitive value chains (NSVCs) and looks at how they can produce positive outcomes, not only in terms of generating income but also for improving nutrition for smallholder producers. The Guide was developed using an in-depth participatory and consultative approach. Beginning from available evidence, the NSVC framework was developed, field tested and then validated by national and international experts. The Guide is relevant not only for IFAD but also for others that recognize the critical importance of incorporating nutrition and improving diets through value chain projects. Governments, NGOs, civil society, the private sector, and other institutions and development agencies working in agriculture, food systems, nutrition and rural development will find the Guide useful.